La metodología parvularia y su incidencia en el aprendizaje de los niños y niñas de preparatoria, primer grado de educación general básica de la escuela fiscal Ovidio Decroly de la ciudad de Catamayo en el periodo lectivo 2013- 2014 - Garrido Paladines, Maria Emerita (2014)
This research work, called "Early Childhood METHODOLOGY AND ITS IMPACT ON LEARNING CHILDREN OF SCHOOL, FIRST DEGREE GENERAL EDUCATION BASIC SCHOOL FISCAL" OVIDIO DECROLY "CITY CATAMAYO for school year 2013 - 2014 ". It has been structured and developed in accordance with the Rules of the Academic Board of the National University of Loja. The overall objective, Introduce the teachers and teachers the importance of Preschool Methodology and its impact on the learning of children in School, First Grade Basic Education School Fiscal "Ovidio Decroly" city was formulated Catamayenses, for school year 2013-2014. The methods used were the Scientific, Inductive, Deductive, Descriptive, Analytical Method - Synthetics and Statistical Model. The techniques applied were: the survey of the High School Teachers, Preschool to determine what methodology used in the daily work, and a Guide to Observing children in First Grade Basic Education School Fiscal "Ovid Decroly" to assess the level of learning. App of teachers ranging from pre Survey found that: 100% of the teachers surveyed used in their daily work and play methodology sheets; 67% of the story and the music. According to the results of the observation guide, the following result was obtained: 41% of boys and girls have a level assessed Learning Highly Satisfactory, 44% and 15% Satisfactory Unsatisfactory.